Europe’s cognitive security: generative AI, hybrid conflict and democratic resilience - Marsili, M. (Janus: Anuário de relações exteriores, 2026)
The spread of generative AI, hybrid conflict and foreign information manipulation is reshaping the European security environment. The European Union is responding by moving beyond a narrow counter-disinformation approach towards a broader concept of cognitive security. Yet major gaps remain in enforcement, strategic coherence and democratic resilience.